2003
DOI: 10.1007/s00410-003-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

Importance of water for Archaean granitoid petrology: a comparative study of TTG and potassic granitoids from Barberton Mountain Land, South Africa

Abstract: A new model for Archaean granitoid magmatism is presented which reconciles the most important geochemical similarities and differences between tonalite-trondhjemite-granodiorite (TTG) and potassic granitoids. Trace element abundances reveal a strong arc magmatism signature in all studied granitoids from Barberton Mountain Land. Characteristic features include HFSE depletion as well as distinct enrichment peaks of fluid-sensitive trace elements such as Pb in N-MORB normalisation, clearly indicating that all stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(40 citation statements)
references
References 45 publications
(94 reference statements)
1
39
0
Order By: Relevance
“…Rocks with adequate trace element concentrations are produced after 70-90 vol% fractionation, resulting in volumetrically important amounts of granitoids. Furthermore, the modeled trace element characteristics of Group 2 granitoids are essentially identical to those observed in many Archean TTG gneisses, indicating that high-pressure hydrous fractionation of garnet-bearing lithologies in the lower arc crust could lead to the formation of TTG suites in accordance with the model proposed by Kleinhanns et al (2003).…”
Section: Chemical Model Of Magma Differentiationsupporting
confidence: 71%
See 1 more Smart Citation
“…Rocks with adequate trace element concentrations are produced after 70-90 vol% fractionation, resulting in volumetrically important amounts of granitoids. Furthermore, the modeled trace element characteristics of Group 2 granitoids are essentially identical to those observed in many Archean TTG gneisses, indicating that high-pressure hydrous fractionation of garnet-bearing lithologies in the lower arc crust could lead to the formation of TTG suites in accordance with the model proposed by Kleinhanns et al (2003).…”
Section: Chemical Model Of Magma Differentiationsupporting
confidence: 71%
“…Accordingly, granitoids, including the TTG suite, could equally be formed by derivative liquids resulting from hydrous fractional crystallization of basaltic melts at medium to high pressure (e.g., Jagoutz 2010; Kleinhanns et al 2003). Interestingly, even though a pressure dependence of the Na concentration of partial melts has been postulated, experimental data indicate that the high Na/K composition of Archean TTG granites cannot be explained by partial melting or fractional crystallization processes at different depths alone (Moyen and Stevens 2006).…”
mentioning
confidence: 99%
“…TTG suites and GGM .suites have strong similarities such as over enrichment in fluid sensitive elements such as Pb (Martin, 1994;Kleinhans et al, 2003). KJeinhans et al (2003) suggested the characteristic features of TTG's include HESE depletion and distinct Pb enrichment signature seen on the chondrite-normalised REE diagram, as reflected in all JD suites, is evidence that these rocks are derived frotn refertilised mantle above subducion zones.…”
Section: Discussion Of Likely Tectonic Setting Peterogenesismentioning
confidence: 99%
“…Average of 31 Closepet-typf granites (<62% SiOjJ (Martin et al, 2005) 7. Nelspruit pluton (Kleinhans et al, 2003) 8. Average of 267 High Silica Atlakitcs (Martin et al, 2005) 9.…”
Section: Figure 8 the Various Plutonic Units Of Tbe Fd Plotted On Thmentioning
confidence: 99%
See 1 more Smart Citation